Analysis of risk factors for hypertension in the community in the working area of the Sigumpar Health Center, Sigumpar District Toba Regency in 2022 - Minar Lenny Situmorang (International Journal of Health Engineering and Technology, 2023)
Hypertension is a disease that occurs when a person's blood pressure increases > 140 mmHg and/or diastolic blood pressure > 90 mmHg. Data from the North Sumatra Provincial Health Office in 2018, hypertension was ranked first out of the 10 most common diseases, namely 70,195 new cases and 184,946 old cases and the most at the Sigumpar Health Center with 585 cases, but in 2020 the incidence of hypertension increased to 1,371 cases. This study aims to analyze the relationship between gender, age, smoking habits, physical activity and fruit and vegetable consumption with the incidence of hypertension in the community in the working area of ​​the Sigumpar Health Center. The research design is analytic observational with a cross sectional approach. The place of this research is in the working area of ​​the Sigumpar Health Center and the time of the research is November 2022. The population in this study is all people in the working area of ​​the Sigumpar Health Center. The sampling technique uses a non-probability sampling technique with consideration of the completeness of patient data. The instrument used was an early detection questionnaire. The dependent variable was the incidence of hypertension and the independent variables were age, gender, smoking habits, physical activity and fruit and vegetable consumption. Data analysis used the chi square test. The results showed that there was a relationship between age (p-value 0.0001) and the incidence of hypertension, while gender, smoking habits, physical activity and fruit and vegetable consumption showed no relationship with the incidence of hypertension.